Solve for y 3*-7=-6y-28

Math
3⋅-7=-6y-28
Rewrite the equation as -6y-28=3⋅-7.
-6y-28=3⋅-7
Multiply 3 by -7.
-6y-28=-21
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Add 28 to both sides of the equation.
-6y=-21+28
Add -21 and 28.
-6y=7
-6y=7
Divide each term by -6 and simplify.
Tap for more steps…
Divide each term in -6y=7 by -6.
-6y-6=7-6
Cancel the common factor of -6.
Tap for more steps…
Cancel the common factor.
-6y-6=7-6
Divide y by 1.
y=7-6
y=7-6
Move the negative in front of the fraction.
y=-76
y=-76
The result can be shown in multiple forms.
Exact Form:
y=-76
Decimal Form:
y=-1.16‾
Mixed Number Form:
y=-116
Solve for y 3*-7=-6y-28

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top